PENGUJIAN USER ACCEPTANCE TEST PADA APLIKASI BANGBELI: (STUDI KASUS: PT. DOA ANAK DIGITAL) - I Dewa Gde Satria Pramana Erlangga; Sugiarto Sugiarto; Afina Lina Nurlaili (Pusat Riset dan Inovasi Nasional, 2023)
The development of the Bangbeli application is one of the efforts to increase the number of users. However, to ensure that these changes and additions meet the users' needs, user validation is required to verify that the developed application meets the defined business requirements and functionalities, thereby providing benefits to both the company and end users. User acceptance testing aims to determine the respondents' feedback on a system that has been created. The results of this testing yield the user acceptance test results, which consist of three aspects: design interface, user-friendliness, and efficiency. The agreement percentages for each aspect are 69.64%, 71.12%, and 68.76% respectively.